Controle para bombeamento distribuído com vistas à minimização dos custos energéticos aplicado a sistemas de abastecimento de água - Carvalho, Paulo Sergio Oliveira de (2012)
The objective of this research was to develop a nonlinear controller, using the technique of fuzzy intelligent control, apply to networks pressurized water distribution sectored, automated and distributed pumping system in order to minimize energy consumption. The methodology used was based on the performance of several tests using an instrumented experimental network, where the control system can be tested and evaluated. The experimental system has pressure transducers and flow, variable speed driven, proportional control valves and water distribution lines, with different topologies that allow you to simulate dynamically different situations operational supply network, depending on the variation of demand water over time. The supervisory system built acquires the necessary data, provided by the network monitoring tools. The controller module of the supervisory system processes data in real time, tuning the instruments to carefully control the experimental network. We performed numerous tests with different operating conditions in order to extract rules and various combinations of control, to optimize the balance of pressures on the network and reduce energy consumption. The results obtained proved that it is more economical to operate the network with the two sets of pumping, for all ranges of consumption studied. Besides the economic aspect, which indicated an energy saving of around 12.17%, the controller gave better performance to achieve and balance the pressures of the network with the pumping action of two acting simultaneously.